A Case Report on Unfolding the Strange Mystery of PMS Triggering Extreme Behavior in Women - Bemina JA; Thereza Mathais (RGUHS Journal of Nursing Sciences)
Reproductive health is a state of complete physical mental and social well-being during which the reproductive process is carried out. It is not just the absence of sickness or diseases of the reproductive process. Apart from the physical discomfort related to the menstrual cycle most women suffer changes in mood and behavior. Although the cycle has both highs and lows premenstrual syndrome PMS is a term used to describe the most difficult side of the menstrual cycle. The presence of PMS symptoms alone is typically not regarded as stressful or incapacitating even though PMS reduces quality of life and social functioning. Nonetheless this is a poorly understood health concern particularly in the workplace setting. The aim of this article was to present a case on unfolding the strange mysteries of PMS and its effective management with mindfulness-based cognitive behavioral therapy.